The aids booklet - Cox, Frank D. ([S.l.] : McGraw-Hill Humanities/Social Sciences/Languages, 1999)
This booklet provides current facts about AIDS and HIV: what it is, how the virus is transmitted, its prevalence among various population groups, symptoms of HIV infection, strategies for prevention, etc. It also covers the legal, social, medical, and ethical issues related to AIDS and HIV. After publication, additional updates are posted to the website at http://www.mhhe.com/catalogs/sem/hhp/student. It is available for $1.00 when combined with any McGraw-Hill product to create a package.
Keywords: medical science,aids